2019
DOI: 10.1186/s10020-019-0075-4
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of SAA1 inhibits palmitate- or high-fat diet induced insulin resistance through suppression of the NF-κB pathway

Abstract: Background Obesity is one of the leading causes of insulin resistance. Accumulating reports have highlighted that serum amyloid A-1 (SAA1) is a potential candidate that is capable of attenuating insulin resistance. Hence, we conducted the current study with aims of investigating our proposed hypothesis that silencing SAA1 could inhibit the progression of obesity-induced insulin resistance through the NF-κB pathway. Methods Gene expression microarray analysis was initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…These results suggest that a possible combination of AICAR and an inhibitor of mTOR, such as rapamycin, or other PI3K/AKT/mTOR pathway inhibitors might be beneficial in the treatment of childhood leukemias [192]. In bladder cancer, AICAR enhanced growth inhibition and cellular apoptosis induced by 10-hydroxycamptothecin in T24 and 5637 bladder cancer cell lines [193].…”
Section: Aicarmentioning
confidence: 90%
“…These results suggest that a possible combination of AICAR and an inhibitor of mTOR, such as rapamycin, or other PI3K/AKT/mTOR pathway inhibitors might be beneficial in the treatment of childhood leukemias [192]. In bladder cancer, AICAR enhanced growth inhibition and cellular apoptosis induced by 10-hydroxycamptothecin in T24 and 5637 bladder cancer cell lines [193].…”
Section: Aicarmentioning
confidence: 90%
“…SAA1, namely, serum amyloid A-1 protein belongs to the SAA family ( 39 ). As a classical acute-phase protein produced by hepatocytes, SAA mediated infection, injury, and inflammation response and could regulate toll-like receptor 4 (TLR4), which participated in obesity-induced insulin resistance ( 40 ). In progressive liver diseases, including NASH, the serum level of SAA could serve as a biomarker for inflammatory status ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Emmens et al [39] found that PENK (proenkephalin) expression was up regulated in cardiovascular diseases, but this gene might be responsible for progression of T2DM. Recent studies have proposed that the SAA1 [40], SUCNR1 [41], CRP (C-reactive protein) [42], APCS (amyloid P component, serum) [43], PCK1 [44], IGF2BP3 [45], POSTN (periostin) [46] and COL6A3 [47] are associated with progression of T2DM. CARTPT (CART prepropeptide) [48], SEMA3C [49] and TDO2 [50] were proved to participate in the development of obesity, but these genes might be linked with progression of T2DM.…”
Section: Discussionmentioning
confidence: 99%